STUDENT'S PERCEPTION ANALYSIS OF THE APPLICATION OF THE SELF-LEARNING LEARNING MODEL IN LEARNING - Heri Suryaman; Florentino Marino Ade Setiawan Nabi (Universitas Nahdatul Ulama Surabaya, 2021)
The purpose of the following research is to obtain student perceptions of the application of the Self-Regulated Learning learning model in class XI DPIB at SMKN 1 Kediri. Self-Regulated Learning in this study with three main factors according to Zimmerman, namely individual factors that have a relationship with student self-efficacy, behavioral factors that have a relationship with self-observation, self-reaction, and environmental factors. This type of quantitative descriptive research uses survey methods. The data collection technique was carried out using a questionnaire instrument. The data analysis technique was descriptive statistics using the percentage formula. The population in this study was 71 students through the use of the Proportional Random Sampling technique. Certainty of the number of tests, i.e. if the population is small, below 100, is considered a population study because the entire population is taken as a test-test. The findings of the study indicate that the perceptions of students in class XI DPIB are in the very positive category 0%, the positive category 50.70%, the medium category 23.94%, the negative category 18.31%, and the very negative category 7.04%. The positive results are given the conclusion that most of the students of class XI DPIB at SMK Negeri 1 Kediri have high Self-Regulated Learning and can self-regulate to achieve learning goals.